Critique of Artificial Reason: Ontology of Human and Artificial Intelligence - Lee, Dr. Yoochul (Journal of Ecohumanism, 2025)
This study delves into the philosophical implications of artificial intelligence (AI) and its divergence from human cognition. As AI becomes a central force in global technological advancement, concerns arise about its potential to surpass human control. Historically, debates have focused on strong vs. weak AI, often rooted in human-centric perspectives. This research challenges these views, proposing that AI's distinct nature from human intelligence is not a limitation but a strength. By exploring the metaphysical assumptions and ontological differences between humans and AI, this study aims to redefine AI's role beyond mere human imitation. It critiques AI through historical frameworks of reason and examines claims of equivalence between AI and human cognition. Ultimately, the research seeks to establish a philosophical foundation for international AI norms, addressing both its potential and ethical considerations.